The profile of upper integument lip of Baduy and the nearby living Sundanese in South Banten, West Java, Indonesia - Rachman Ardan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Based on the Two Migration Theory and on cultural anthropology, the Baduy is classified as Protomalay and the Sundanese as Deuteromalay. Historically and socioculturally the Baduy is part of the Nearby Living Sundanese (NS) who has isolated themselves and settled down in Kanekes. Linguistics and archaeology could not tell whether the culture’s spread was due to a source population’s migrating or to a destination population’s copying the technology and language. Craniofacial anthropometry could resolve this because people’s physiognomy does not change rapidly due to mere migration. Purpose: The objective of this study is to determine whether the people of Baduy are Protomalay or Deuteromalay based on Profile of Upper Integument Lips (PUIL), which is the size of the angle formed by (sn-Ls) line to Frankfurt Horizontal Plane. Angle size < 90º = Procheili, 90º = Orthocheili, and > 90º = Opisthocheili. Lip prominence is strongly influenced by racial and ethnical characteristics, its form is determined especially by genetic factor. Method: Subject sample consisted of 43 Inner Baduys (IB); 92 Outer Baduys (OB); and 135 NS of South Banten were measured using Fasiogoniometer to determine PUIL. Average value data was determined and analyzed by Testing Equal Variances to compare two variances between groups. Result: The result of this study showed that IB, OB as well as NS are Mild Procheili (angle size = 50º–69.9º). PUIL of IB and OB compared to NS are slightly different, however, between IB and OB are similar. Conclusion: Based on the characteristic of PUIL, IB, OB, as well as NS, are classified as Mongoloid subrace, and physically should be classified as Deuteromalay.